Multifocal early gastric cancer in a patient with autoimmune atrophic gastritis and iron deficiency anaemia - Neesse, A.; Michl, P.; Barth, P.; Vieth, M.; Langer, P.; Ellenrieder, V.; Gress, T. M. (TumorDiagnostik & Therapie, 2009)
Autoimmune atrophic gastritis (AMAG) is characterised by the presence of parietal cell antibodies (PCA) and occurs in the gastric corpus. Pernicious anaemia (PA) is regarded as the most distinct feature and sequela of AMAG and is associated with the presence of PCA in about 60 90 % of cases. AMAG is considered as an independent risk factor for the development of gastric cancer. Interestingly, the risk to progress from metaplasia to neoplasia and ultimately invasive cancer has exclusively been described in patients with PA. However, AMAG can also occur in the absence of PA, sometimes even in association with other haematological manifestations such as iron deficiency anaemia (IDA). This is the first report of a patient with AMAG associated with IDA and the development of multifocal early gastric cancer only three years after initial diagnosis. Furthermore, our patient showed an atypical morphological distribution pattern of atrophic mucosa with involvement of both the gastric corpus and the antrum. H. pylori infection as a cause for the involvement of the antrum could be repeatedly excluded by breath test, histology and serological testing for H. pylori antibodies. In summary, the presence of IDA together with an atypical distribution pattern of AMAG may represent predictors for the individual risk to progress to gastric cancer and should be taken into account in surveillance strategies. © Georg Thieme Verlag KG Stuttgart.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Autoimmune atrophic gastritis; Gastric cancer; H. pylori; Iron deficiency anaemia; Metaplastic atrophic gastritis; Multifocal early gastric cancer; Pernicious anaemia